Aptamer-Based Therapeutics: New Approaches to Combat Human Viral Diseases - Ka-To Shum; Jiehua Zhou; John J. Rossi (MDPI AG, 2013)
Viruses replicate inside the cells of an organism and continuously evolve to contend with an ever-changing environment. Many life-threatening diseases, such as AIDS, SARS, hepatitis and some cancers, are caused by viruses. Because viruses have small genome sizes and high mutability, there is currently a lack of and an urgent need for effective treatment for many viral pathogens. One approach that has recently received much attention is aptamer-based therapeutics. Aptamer technology has high target specificity and versatility, i.e., any viral proteins could potentially be targeted. Consequently, new aptamer-based therapeutics have the potential to lead a revolution in the development of anti-infective drugs. Additionally, aptamers can potentially bind any targets and any pathogen that is theoretically amenable to rapid targeting, making aptamers invaluable tools for treating a wide range of diseases. This review will provide a broad, comprehensive overview of viral therapies that use aptamers. The aptamer selection process will be described, followed by an explanation of the potential for treating virus infection by aptamers. Recent progress and prospective use of aptamers against a large variety of human viruses, such as HIV-1, HCV, HBV, SCoV, Rabies virus, HPV, HSV and influenza virus, with particular focus on clinical development of aptamers will also be described. Finally, we will discuss the challenges of advancing antiviral aptamer therapeutics and prospects for future success.